2018
DOI: 10.1097/md.0000000000011100
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-221 from tissue may predict the prognosis of patients with osteosarcoma

Abstract: This study was aimed to investigate the relationship between miR-221 expression and prognosis in patients with osteosarcoma.miR-221 expression in 69 osteosarcoma specimens and corresponding noncancer tissues were characterized by quantitative reverse transcription polymerase chain reaction. The associations of miR-221 expression with clinicopathologic factors and prognosis in patients with osteosarcoma were statistically analyzed.miR-221 expression in patients with osteosarcoma was significantly higher than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 47 publications
(33 reference statements)
0
26
0
Order By: Relevance
“…Then, the entire text of the remaining 362 studies was assessed, determining the removal of 312 further studies. Finally, 50 articles, published between 2009 and 2018, were included in the systematic review [35,36,37,38,39,40,41,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93]. A detailed flow-chart illustrating the literature selection process is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the entire text of the remaining 362 studies was assessed, determining the removal of 312 further studies. Finally, 50 articles, published between 2009 and 2018, were included in the systematic review [35,36,37,38,39,40,41,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93]. A detailed flow-chart illustrating the literature selection process is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The main general information on the included studies are reported in Table 1 and Table 2. Among them, 27 focused on miR-221 [36,38,40,52,54,57,60,61,62,64,69,70,72,73,74,75,79,80,81,82,83,84,85,88,89,91,92], 11 on miR-222 [37,39,53,56,59,63,67,68,86,87,93], and the remaining 12 investigated the cluster miR-221/miR-222 [35,41,51,55,58,65,66,71,76,77,78,90]. Overall, 6086 patients suffering from different tumors were included in the systematic review, with the sample size in each study ranging from 20 to 393 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The upregulation of miR-221 can predict clinical outcomes in patients with OS. 25 miR-629 has been shown to be abnormally expressed in a variety of cancers and can be used as a prognostic and diagnostic marker for tumors. miR-629 can be used as a molecular marker for the diagnosis and prognosis of pancreatic cancer.…”
Section: Figurementioning
confidence: 99%
“…A study conducted by Liu et al shows that the miR-29 is upregulated in OS and promotes cell proliferation and migration [ 10 ]. The expression of miR-221 is increased in patients with OS and identified as a promising prognostic indicator [ 11 ]. Additionally, the serum miR-124, miR-101, and miR-30c were remarkably down-regulated in OS patients and might act as tumor suppressors [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%